Compositional and physicochemical factors governing the viability of Lactobacillus rhamnosus GG embedded in starch-protein based edible films - Soukoulis, Christos; Singh, Poonam; Macnaughtan, William; Parmenter, Christopher D.J.; Fisk, Ian D. (Elsevier, 2015)
Probiotic incorporation in edible films and coatings has been shown recently to be an efficient strategy for the delivery of probiotics in foods. In the present work, the impact of the compositional, physicochemical and structural properties of binary starch-protein edible films on Lactobacillus rhamnosus GG viability and stability was evaluated. Native rice and corn starch, as well as bovine skin gelatine, sodium caseinate and soy protein concentrate were used for the fabrication of the probiotic edible films. Starch and protein type both impacted the structural, mechanical, optical and thermal properties of the films, and the process loss of L. rhamnosus GG during evaporation-dehydration was significantly lower in the presence of proteins (0.91–1.07 log CFU/g) compared to solely starch based systems (1.71 log CFU/g). A synergistic action between rice starch and proteins was detected when monitoring the viability of L. rhamnosus GG over four weeks at fridge and room temperature conditions. In particular, a 3- to 7-fold increase in the viability of L. rhamnosus GG was observed in the presence of proteins, with sodium caseinate – rice starch based films offering the most enhanced stability. The film's shelf-life (as calculated using the FAO/WHO (2011) basis of 6 log viable CFU/g) ranged between 27-96 and 15–24 days for systems stored at fridge or room temperature conditions respectively.